2014
DOI: 10.1371/journal.pone.0103979
|View full text |Cite
|
Sign up to set email alerts
|

No Adjuvant Effect of Bacillus thuringiensis-Maize on Allergic Responses in Mice

Abstract: Genetically modified (GM) foods are evaluated carefully for their ability to induce allergic disease. However, few studies have tested the capacity of a GM food to act as an adjuvant, i.e. influencing allergic responses to other unrelated allergens at acute onset and in individuals with pre-existing allergy. We sought to evaluate the effect of short-term feeding of GM Bacillus thuringiensis (Bt)-maize (MON810) on the initiation and relapse of allergic asthma in mice. BALB/c mice were provided a diet containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Neither the trypCry1Ab protein nor pollen or leaf extract from MON810 maize plants promoted systemic immune responses against OVA, as shown by low levels of all endpoints. These findings, although a different route of exposure was applied, are in line with the recently published study by Reiner et al . In that study, feeding of MON810‐containing diets for up to 34 days did not affect OVA‐induced eosinophilic lung inflammation, or OVA‐specific antibody production, using a mouse model of allergic asthma.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Neither the trypCry1Ab protein nor pollen or leaf extract from MON810 maize plants promoted systemic immune responses against OVA, as shown by low levels of all endpoints. These findings, although a different route of exposure was applied, are in line with the recently published study by Reiner et al . In that study, feeding of MON810‐containing diets for up to 34 days did not affect OVA‐induced eosinophilic lung inflammation, or OVA‐specific antibody production, using a mouse model of allergic asthma.…”
Section: Discussionsupporting
confidence: 90%
“… reported a potential adjuvant effect, as oral gavage of the trypsinized version of Cry1Ab plus a major food allergen showed increased Th2 and Th17 cytokine production and eosinophil inflammation in the airways of mice. In contrast, a recent study found no adjuvant effects on the onset or severity of allergic asthma after short‐term feeding of mice to a MON810 maize diet.…”
Section: Introductionmentioning
confidence: 73%
“…It is noted that the EFSA GMO Panel has discussed extensively the potential allergenic and adjuvant capacity of some Cry proteins considering all available information, including literature on the topic (e.g. Vazquez-Padron et al, 1999;Moreno-Fierros et al, 2003;Rojas-Hernandez et al, 2004;Guimaraes et al, 2008;Reiner et al, 2014;Andreassen et al, 2015aAndreassen et al, ,b, 2016Torres-Martinez et al, 2016;Santos-Vigil et al, 2018). In particular, the adjuvant capacity of Cry proteins is a matter of current scientific debate, where most of the scientists agree on the limited and contrasting evidence available (Rubio-Infante and Moreno-Fierros 2015; Joshi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that airway exposure to different versions of the trypCry1Ab protein did not promote allergic responses comparable to those observed with the inclusion of an adjuvant (CT) in mice sensitised with the allergen ovalbumin (OVA) [ 25 ]. Furthermore, a recent study by Reiner et al [ 20 ] investigated the initiation and severity of allergic asthma in mice fed a MON810 containing diet, and they were not able to detect any differences in eosinophilic airway and lung inflammation, mucus hypersecretion or OVA-specific antibody production, compared to mice given a non-GM diet. Taken together with the previous study, our present data from a clinical food allergy model further support the notion that trypCry1Ab do not promote development of immune responses towards another allergen, i.e., exerts allergic adjuvant effect.…”
Section: Discussionmentioning
confidence: 99%
“…The structurally similar Cry1Ac protein has demonstrated adjuvant capacity in several studies [ 17 19 ]. To our knowledge, only three studies have investigated allergic adjuvant effects of Cry1Ab, reporting no [ 20 , 21 ] and possible [ 22 ] adjuvant capacity after exposure by airways installation, feeding and oral gavage, respectively. So far, no experimental studies have investigated whether Cry proteins have adjuvant properties in relation to clinical food allergy responses.…”
Section: Introductionmentioning
confidence: 99%